UPPER CUTTING TOOL TO INCREASE SLIPPER PRODUCTION IN KOTALAMA VILLAGE, KEDUNGKANDANG DISTRICT, MALANG CITY - Nuriyanti, Ika; Ingsih, Ita Suhermin; Wafi, Abdul (LPPM Univ. Ibn Khaldun Bogor, 2023)
This community service is carried out to entrepreneurs in the slipper's home industry, precisely in Kotalama Village, Kedungkandang District, Malang City. The micro-business developing in this village manufactures slippers, which only absorbs 3 to 6 workers. IRT